Tribal Cultural Heritage and Environmental Sustainability: Global Insights from Indigenous Knowledge Systems - Pangi Vijaya Nirmala,; Abhinash Marukurti,; Sheik Shariff,; Koppisetti Gayathri,; K Chandra Sekhar, (IJRDO - Journal of Social Science and Humanities Research, 2025)
The present review aims to examine the global role of tribal and Indigenous cultural practices in promoting environmental sustainability. Across continents, Indigenous and tribal communities have maintained ecological balance through traditional ecological knowledge (TEK) systems that integrate cultural values, spirituality, and environmental ethics. These systems encompass practices such as sacred grove protection, controlled burning, agroforestry, rotational grazing, and customary water management, all of which embody sustainable principles refined through generations of adaptation. Drawing on studies from Africa, Asia, Australia, and the Americas, the review highlights how community-based governance and Indigenous stewardship contribute to biodiversity conservation, climate resilience, and sustainable resource management. It further discusses how contemporary environmental frameworks, including the Convention on Biological Diversity (CBD) and the Sustainable Development Goals (SDGs), are increasingly recognizing the value of TEK in achieving global sustainability targets. However, the integration of Indigenous knowledge into policy remains challenged by epistemological gaps, power asymmetries, and cultural marginalization. The review emphasizes the need for co-designed governance models that ensure Indigenous participation, protect intellectual property rights, and preserve cultural autonomy. By recognizing tribal heritage as a living source of ecological wisdom rather than an antiquated tradition, this review underscores the relevance of Indigenous worldviews in addressing modern environmental crises and shaping equitable, resilient, and culturally grounded pathways toward sustainability.